2022
DOI: 10.3390/cancers14225597
|View full text |Cite
|
Sign up to set email alerts
|

The NAMPT Inhibitor FK866 Increases Metformin Sensitivity in Pancreatic Cancer Cells

Abstract: Pancreatic cancer (pancreatic ductal adenocarcinoma: PDAC) is one of the most aggressive neoplastic diseases. Metformin use has been associated with reduced pancreatic cancer incidence and better survival in diabetics. Metformin has been shown to inhibit PDAC cells growth and survival, both in vitro and in vivo. However, clinical trials using metformin have failed to reduce pancreatic cancer progression in patients, raising important questions about molecular mechanisms that protect tumor cells from the antine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Here, we will just remind the reader that the last two years have witnessed the emergence of new small-molecule chemical NAMPT inhibitors that exhibited very potent anticancer activity against hematological malignancies with IC50 values in the picomolar range [56][57][58]. A synergistic interaction between FK866 and the antidiabetic drug metformin was also recently reported in pancreatic cancer cells [59]. In addition to the conventional small-molecule inhibitors that block NAMPT enzymatic activity, one of the most promising approaches that have recently emerged is to degrade NAMPT by triggering its ubiquitin-mediated proteolysis.…”
Section: Targeting Nicotinamide Phosphoribosyltransferasementioning
confidence: 94%
“…Here, we will just remind the reader that the last two years have witnessed the emergence of new small-molecule chemical NAMPT inhibitors that exhibited very potent anticancer activity against hematological malignancies with IC50 values in the picomolar range [56][57][58]. A synergistic interaction between FK866 and the antidiabetic drug metformin was also recently reported in pancreatic cancer cells [59]. In addition to the conventional small-molecule inhibitors that block NAMPT enzymatic activity, one of the most promising approaches that have recently emerged is to degrade NAMPT by triggering its ubiquitin-mediated proteolysis.…”
Section: Targeting Nicotinamide Phosphoribosyltransferasementioning
confidence: 94%
“…Maintenance of NAD+/NADH homoeostasis affects metformin sensitivity in various cancer cell lines 77 . Furthermore, an in-vitro analysis has shown that the nicotinamide phosphoribosyltransferase (NAMPT) inhibitor FK866 sensitized PDAC cells to metformin’s antiproliferative actions and lowered the cellular NAD+ pool 78 .…”
Section: The Effect Of Anti-diabetics On Systematic Treatment Of Panc...mentioning
confidence: 99%
“…This synergy hinges on a lowered NAD + /NADH ratio, driving cells to ramp up NAD biosynthesis. [143] This suggests that dual targeting of mitochondria and NAD biosynthesis may result in effective antitumor therapies.…”
Section: Therapeutic Targeting Of Pdac Metabolismmentioning
confidence: 99%